Hodgkin's disease in the nasopharynx - (:unkn) unknown (My University, 2006)
Nasopharyngeal presentation of Hodgkin's disease (HD) is an uncommon event with relatively favorable prognosis. It is predominantly seen in males and most papers are case reports. Here, we report an unusual case in a female patient with stage IA(E)HD treated by radiotherapy (RT), and achieving complete disease remission, lasting 26(+) months.
Keywords: Female; Humans; Middle Aged; Disease-Free Survival; Hodgkin Disease; Nasopharyngeal Neoplasms